Atomic Interface Catalytically Synthesizing SnP/CoP Hetero-Nanocrystals within Dual-Carbon Hybrids for Ultrafast Lithium-Ion Batteries. (November 2022) - Hu, Chen; Hu, Yanjie; Chen, Aiping; Duan, Xuezhi; Jiang, Hao; Li, Chunzhong
Graphical abstract: Abstract: Tin phosphides are attractive anode materials for ultrafast lithium-ion batteries (LIBs) because of their ultrahigh Li-ion diffusion capability and large theoretical-specific capacity. However, difficulties in synthesis and large size enabling electrochemical irreversibility impede their applications. Herein, an in situ catalytic phosphorization strategy is developed to synthesize SnP/CoP hetero-nanocrystals within reduced graphene oxide (rGO)-coated carbon frameworks, in which the SnP relative formation energy is significantly decreased according to density functional theory (DFT) calculations. The optimized hybrids exhibit ultrafast charge/discharge capability (260 mA·h·g −1 at 50 A·g − 1 ) without capacity fading (645 mA·h·g − 1 at 2 A·g − 1 ) through 1500 cycles. The lithiation/delithiation mechanism is disclosed, showing that the 4.0 nm sized SnP/CoP nanocrystals possess a very high reversibility and that the previously formed metallic Co of CoP at a relatively high potential accelerates the subsequent reaction kinetics of SnP, hence endowing them with ultrafast charge/discharge capability, which is further verified by the relative dynamic current density distributions according to the finite element analysis.